Maladministrasi Dalam Bidang Pendidikan di Indonesia - Ohorella, Muhammad Fawwaz; Nirahua, Salmon Eliazer Marthen; Nendissa, Renny Heronia (PATTIMURA Law Study Review, 2025)
The legal issue in this study is the finding of intolerance against students in the school environment, namely the polemic of non-Muslim students at SMK Negeri 2 Padang, West Sumatra who are required to wear hijab. Therefore, it is interesting to examine whether intolerance can be categorized as a form of maladministration so that administrative sanctions can be applied to the action itself. The purpose of this study is to find out and analyze acts of intolerance against female students that can be categorized as maladministration and administrative sanctions that can be applied to acts of intolerance for female students in the school environment. The research method used in this writing is a normative juridical research method with a legislative approach and a conceptual approach. The results of this study can be concluded that Intolerance Actions for female students in the school environment can be categorized as a form of maladministration in the education sector. This is based on Article 1 point 3 of Law Number 37/2008 and Article 11 of Ombudsman Regulation Number 26/2017 which defines maladministration as a form of behavior or unlawful act, one of which is discrimination, on the grounds that it does not provide freedom for students to behave and express their opinions through the way of wearing a uniform in accordance with the religion adhered to and this action is a violation of government administration and public services. Administrative sanctions that can be applied to acts of intolerance for students in the school environment are that they can be subject to disciplinary sanctions based on the rule of law.